Effect of two protocols of cryopreservation on fertilizing capacity of stallion (equus caballus) semen / efecto de dos protocolos de criopreservación sobre la capacidad fecundante de semen equino (equus caballus) (2012)
Semen cryopreservation is a fundamental process for the development of biotechnologies for assisted reproduction in horses. The use of cryopreservation techniques with changes in concentrations and the nature of the cryoprotectant, as well as, the different types of vials for storage of semen, have become an alternative to improve the protocols used. The objective of this work was to evaluate the effect of two protocols of cryopreservation (freezing and vitrification) on the fertilizing capacity of stallion semen. The study was conducted with horses of the Criollo Colombiano breed. For freezing was used a extender supplemented with egg yolk (4%) and dimethyl formamide (5%), and 0.5 mL straws as vials, whereas for vitrification, the extender was supplemented with egg yolk (8%) and dimethyl formamide (8%), and cryovials were used as carriers. As post thaw parameters were evaluated: progressive motility, vitality, normal morphology and integrity of the plasma membrane through the hypoosmotic swelling test (HOS). For statistical evaluation was fitted a generalized linear model (GLM) and means were compared by the Tukey test. Were found average percentages of progressive motility, vitality, normal morphology and HOS of 41.6 ± 11.8 and 37 ± 8.5, 54.3 ± 10.2 and 52.3 ± 7.8, 83.1 ± 5.4 and 83.6 ± 5.8, 41.7 ± 9.8 and 38.9 ± 3.6, for cryopreserved semen by freezing and vitrification, respectively. There were no statistically significant differences (P ≤ 0.05) between treatments for any of the parameters evaluated. The fertilizing capacity of equine semen cryopreserved by vitrification is comparable to that obtained by conventional freezing. / La criopreservación de semen es un proceso fundamental en el desarrollo de biotecnologías para la reproducción asistida en equinos. El uso de diferentes técnicas de criopreservación con cambios en las concentraciones y la naturaleza de los crioprotectores, así como en los diferentes tipos de soportes para el almacenamiento del semen, se ha constituido en una alternativa para mejorar los protocolos empleados. El objetivo de este trabajo fue evaluar el efecto de dos protocolos de criopreservación (congelación y vitrificación), sobre la capacidad fecundante del semen equino. El estudio se realizó con equinos de la raza Criollo Colombiano. Para la congelación se empleó un diluyente suplementado con de yema de huevo (4%) y dimetilformamida (5%), y pajillas de 0,5 mL como soportes; mientras que para la vitrificación, el diluyente fue suplementado con yema de huevo (8%) y dimetilformamida (8%) y se usaron crioviales como soportes. Post-descongelación, se evaluaron los parámetros: movilidad progresiva, vitalidad, morfología normal e integridad de la membrana plasmática (HOS). Para la evaluación estadística se ajustó un modelo lineal generalizado (GLM) y las medias se compararon por la prueba de Tukey. Se encontraron porcentajes promedio de movilidad progresiva, vitalidad, morfología normal y HOS de 41,6±11,8 y 37,0±8,5, 54,3±10,2 y 52,3±7,8, 83,1±5,4 y 83,6±5,8, 41,7±9,8 y 38,9±3,6, para el semen criopreservado por congelación y vitrificación, respectivamente. No se encontraron diferencias estadísticamente significativas (P ≤ 0,05) entre los tratamientos para ninguno de los parámetros evaluados. La capacidad fecundante del semen equino criopreservado por vitrificación es equiparable a la obtenida por congelación convencional.